Tall cell papillary thyroid carcinoma: new diagnostic criteria and mutations in BRAF and TERT - Dettmer, Matthias S.; Schmitt, Anja; Steinert, Hans; Capper, David; Moch, Holger; Komminoth, Paul; Perren, Aurel (Endocrine related cancer, 2015)
The tall cell (TC) variant of papillary thyroid carcinoma (PTC) has an unfavorable prognosis. The diagnostic criteria remain inconsistent, and the role of a minor TC component is unclear. Molecular diagnostic markers are not available; however, there are two potential candidates: BRAF V600E and telomerase reverse transcriptase (TERT) promoter mutations. Using a novel approach, we enriched a collective with PTCs that harbored an adverse outcome, which overcame the limited statistical power of most studies. This enabled us to review 125 PTC patients, 57 of which had an adverse outcome. The proportion of TCs that constituted a poor prognosis was assessed. All of the tumors underwent sequencing for TERT promoter and BRAF V600E mutational status and were stained with an antibody to detect the BRAF V600E mutation. A 10% cutoff for TCs was significantly associated with advanced tumor stage and lymph node metastasis. Multivariate analysis showed that TCs above 10% were the only significant factor for overall, tumor-specific, and relapse-free survival. Seven percent of the cases had a TERT promoter mutation, whereas 61% demonstrated a BRAF mutation. The presence of TC was significantly associated with TERT promoter and BRAF mutations. TERT predicted highly significant tumor relapse (P<0.001). PTCs comprised of at least 10% TCs are associated with an adverse clinical outcome and should be reported accordingly. BRAF did not influence patient outcome. Nevertheless, a positive status should encourage the search for TCs. TERT promoter mutations are a strong predictor of tumor relapse, but their role as a surrogate marker for TCs is limited.